Testing the Organization of Lower‐Band Whistler‐Mode Chorus Wave Properties by Plasmapause Location. Issue 1 (29th December 2020) - Malaspina, David M.; Jaynes, Allison N.; Elkington, Scot; Chan, Anthony; Hospodarsky, George; Wygant, John
Abstract: Lower‐band whistler‐mode chorus waves are important to the dynamics of Earth's radiation belts, playing a key role in accelerating seed population electrons (hundreds of keV) to relativistic (>1 MeV) energies, and in scattering electrons such that they precipitate into the atmosphere. When constructing and using statistical models of lower‐band whistler‐mode chorus wave power, it is commonly assumed that wave power is spatially distributed with respect to magnetic L‐shell. At the same time, these waves are known to drop in power at the plasmapause, a cold plasma boundary which is dynamic in time and space relative to L‐shell. This study organizes wave power and propagation direction data with respect to distance from the plasmapause location to evaluate what role the location of the plasmapause may play in defining the spatial distribution of lower‐band whistler‐mode chorus wave power. It is found that characteristics of the statistical spatial distribution of equatorial lower‐band whistler‐mode chorus are determined by L‐shell and are largely independent of plasmapause location. The primary physical importance of the plasmapause is to act as an Earthward boundary to lower‐band whistler‐mode chorus wave activity. This behavior is consistent with an equatorial lower‐band whistler‐mode chorus wave power spatial distribution that follows the L‐shell organization of the particles driving wave growth. Plain Language Summary: Whistler‐mode chorus are plasma waves that can efficiently accelerate particles in Earth's radiation belts and act to scatter them out of the radiation belts into Earth's atmosphere. Models of the statistical behavior of these plasma waves are important for predicting the shape of the radiation belts. For decades, wave models relied on the assumption that these particular waves are distributed in space similar to radiation belt particles—by distance from Earth at the magnetic equator. Another possibility is that the spatial distribution of these waves could be modified by the location of Earth's cold plasma torus, the plasmasphere. The plasmasphere moves toward and away from Earth on different time scales than radiation belt particles. This study tests how whistler‐mode chorus plasma waves are organized in space, by comparing statistics of plasma wave properties organized by distance from the Earth at the magnetic equator with the same data organized by distance from the plasmasphere outer boundary. The long‐standing assumption is found to be valid. This result is consistent with the interpretation that the spatial distribution of the plasma waves under study is determined by the spatial organization of the particles that drive the wave growth. Key Points: An often‐used assumption, that whistler‐mode chorus properties are organized by L‐shell, is tested and verified The plasmapause bounds whistler‐mode chorus activity but does not otherwise influence wave property distributions